Strong democracy, weak state: The political economy of Ghana’s stalled structural transformation - Resnick, Danielle (International Food Policy Research Institute, 2016)
What are the political and institutional prerequisites for pursuing policies that contribute to structural transformation? This paper addresses this question by focusing on Ghana, which has achieved sustained economic growth in recent decades and is broadly lauded for its environment of political pluralism, respect for human rights, free and fair elections, and vocal civil society. Yet, despite these virtues, Ghana remains unable to achieve substantial structural transformation as identified as changes in economic productivity driven by value-added within sectors and shifts in the allocation of labor between sectors. This paper argues that Ghana is strongly democratic but plagued by weak state capacity, and these politico-institutional characteristics have shaped the economic policies pursued, including in the agricultural sector, and the resultant development trajectory. Specifically, three political economy factors have undermined Ghana’s ability to achieve substantive structural transformation since then. First, democracy has enabled a broader range of interest groups to permeate policymaking decisions, often resulting in policy backtracking and volatility as well as fiscal deficits around elections that, among other things, stifle credit access for domestic business through high interest rates. Secondly, public sector reforms were not pursued with the same vigor as macroeconomic reforms, meaning that the state has lacked the capacity typically necessary to identify winning industries or to actively facilitate the transition to higher value-added sectors. Thirdly, successive governments, regardless of party, have failed to actively invest in building strong, productive relationships with the private sector, which is a historical legacy of the strong distrust and alienation of the private sector that characterized previous government administrations.